Nickel-Titanium Shape Memory Alloy in Reconstructive Osteosynthesis in Patients With Zygomatico-Orbital Complex Fractures - Petruk, P.S.; Medvedev, Yu.A.; Show Yi, Zhang; Volkova, V.A. (KnE Materials Science, 2017)
At the Department of Maxillofacial Surgery I.M. Sechenov First Moscow State Medical University 120 patients with zygomatico-orbital complex fractures were treated during the period from 2011 to 2015. Different methods of the osteosynthesis are presented and discussed. Successful application experience of superelastic nickelid titanium mesh and porous nickelid titanium implants for the lower orbital wall reconstruction was reviewed.